Association between utilization and quality of antenatal care with stillbirths in four tertiary hospitals in a low‐income urban setting. (9th August 2020) - Gwako, George N.; Were, Fredrick; Obimbo, Moses M.; Kinuthia, John; Gachuno, Onesmus W.; Gichangi, Peter B.
Abstract: Introduction: About 2.6 million stillbirths per year occur globally with 98% occurring in low‐ and middle‐income countries including Kenya, where an estimated 35 000 stillbirths occur annually. Most studies have focused on the direct causes of stillbirth. The aim of this study was to determine the association between antenatal care utilization and quality with stillbirth in a Kenyan set up. This information is key when planning strategies to reduce the stillbirth burden. Material and methods: This was a case‐control study in four urban tertiary hospitals carried out between August 2018 and April 2019. A total of 214 women with stillbirths (cases) and 428 with livebirths (controls) between 28 and 42 weeks were enrolled. Information was obtained through interviews and data abstracted from medical records. Antenatal care utilization was assessed by the proportions of women not attending antenatal care; booking first antenatal care visit in first trimester and not making the requisite four antenatal care visits. Quality of antenatal care was assessed using individual surrogate indicators (antenatal profile testing, weight/blood pressure/urinalysis testing in each antenatal visit, utilization of early obstetric ultrasound, completeness of antenatal records) and a codified indicator made up of seven parameters (attending antenatal care, booking first antenatal care in the first trimester, making four or more antenatal visits, having all antenatal profile tests, having a complete antenatal record, having blood pressure and weight measured at all visits). The association between antenatal care utilization and quality with stillbirth was assessed using univariate and multivariate analysis using logistic regression. Statistical significance was defined as a two‐tailed P value ≤ .05. Results: Women with stillbirth were likely to have a parity ≥4 (19.6% vs 12.6%, P = .02), have an obstetric complication (36% vs 8.6%, P = .001) and have a medical disorder (5.6% vs 1.6%, P = .01). The odds of a stillbirth were four times higher among those who did not attend antenatal care ( odds ratio [OR] 4.1, 95% confidence interval [CI] 1.6‐10, P < .003). Compared with four antenatal care visits, those who had one or two visits had higher odds of a stillbirth: OR 2.96 (95% CI 1.4‐6.1), P = .003, and OR 2.9 (95% CI 1.7‐5), P = .003, respectively. As per the individual surrogate indicators, the likelihood of a stillbirth was lower in women who received good quality antenatal care: Hemoglobin testing (OR 0.6, 95% CI 0.4‐0.8, P = .03), blood group test (OR 0.4, 95% CI 0.2‐0.6, P < .001), HIV test (OR 0.3, 95% CI 0.2‐0.5, P = .001), venereal disease research laboratory test (OR 0.2, 95% CI 0.1‐0.4, P = .001), weight measurement (OR 0.7, 95% CI 0.5‐1.0, P = .047). As per the composite indicator, the quality of antenatal care was poor across the board and there was no association between this surrogate indicator and stillbirth. Conclusions: Lack of antenatal care, attending fewer than four antenatal visits and poor quality antenatal care as measured by surrogate indicators were significantly associated with stillbirth. In addition, women with low education level, obstetric complications, multiparity and medical complications had a significantly higher likelihood of stillbirth. Improving the utilization of four or more antenatal visits and the quality of antenatal care can reduce the risk of stillbirth.